Avaliação do deslintamento químico na qualidade de sementes de algodão - Vaz-Tostes, Douglas Pelegrini (2017)
In cotton ginning, where the fibers are separated from the seeds, it is not possible to remove the portion of short fibers adhered to the seeds, called linter. The linter may impair the quality of the seeds, and may also make it difficult to handle the seeds at the time of sowing. The objective of this work was to evaluate the effects of the application of sulfuric acid in different concentrations and by different times in linter removal, plantability, tegument damage, sanity and quality of cotton seeds.Were used cotton seeds with linter of the variety DP 1536 B2RF, produced in the 2016/2017 crop, provided by the Cooperativa de Produtores Rurais de Catuti, located in the municipality of Catuti, in the north of the state and Minas Gerais The seed lot was physically characterized prior to delinting by determinations of physical purity, linter percentage, thousand seed weight and hectoliter weight. The chemical delinting was done with sulfuric acid (98%) at the doses of 0, 20, 24, 28, 32 and 36 mL in 200 g of seeds with linter and with the stirring times of 2, 7 and 12 minutes. After the delinting was performed the test of plantability and scanning electron microscopy in the seeds. Seed quality was determined by germination, first germination count, emergency speed index, electrical conductivity, sanity test and isoenzymatic activity. The delinting is achieved with the doses of 32 and 36 mL in the times of 7 and 12 minutes. The dose of 32 mL in the time of 12 minutes provides better plantability. There was no significant damage to seed coat. The incidence of fungi is altered with the delinting. The quality of the seeds is improved with the delinting.